2020
DOI: 10.3389/fmicb.2020.564310
|View full text |Cite
|
Sign up to set email alerts
|

Artificially Edited Alleles of the Eukaryotic Translation Initiation Factor 4E1 Gene Differentially Reduce Susceptibility to Cucumber Mosaic Virus and Potato Virus Y in Tomato

Abstract: Eukaryotic translation initiation factors, including eIF4E, are susceptibility factors for viral infection in host plants. Mutation and double-stranded RNA-mediated silencing of tomato eIF4E genes can confer resistance to viruses, particularly members of the Potyvirus genus. Here, we artificially mutated the eIF4E1 gene on chromosome 3 of a commercial cultivar of tomato (Solanum lycopersicum L.) by using CRISPR/Cas9. We obtained three alleles, comprising two deletions of three and nine nucleotides (3DEL and 9D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…Owing to the loss-of-function of the eIF4E protein, the plant lacks one of its most important interaction partners for bymoviruses (Wang and Krishnaswamy, 2012). That mechanism has been reported to confer broad resistance to several bymoviruses in a number of dicotyledonous plants as, for instance, cucumber, tomato and Arabidopsis (Chandrasekaran et al, 2016;Pyott et al, 2016;Atarashi et al, 2020;Moury et al, 2020). However, in a temperate cereal such as barley, the full knock-out of EIF4E was rather expected to be lethal; Yang et al (2016) screened over 2,900 wild and domesticated barley accessions and identified 65 haplotypes for HvEIF4E, of which 19 were associated with resistance to bymoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the loss-of-function of the eIF4E protein, the plant lacks one of its most important interaction partners for bymoviruses (Wang and Krishnaswamy, 2012). That mechanism has been reported to confer broad resistance to several bymoviruses in a number of dicotyledonous plants as, for instance, cucumber, tomato and Arabidopsis (Chandrasekaran et al, 2016;Pyott et al, 2016;Atarashi et al, 2020;Moury et al, 2020). However, in a temperate cereal such as barley, the full knock-out of EIF4E was rather expected to be lethal; Yang et al (2016) screened over 2,900 wild and domesticated barley accessions and identified 65 haplotypes for HvEIF4E, of which 19 were associated with resistance to bymoviruses.…”
Section: Discussionmentioning
confidence: 99%
“…However, for functionally redundant factors, emerging resistance-breaking viruses represent another risk, potentially switching the factor in use from a null to a redundant allele. Moreover, in terms of conferring antiviral resistance, the functional alleles of eIF4E1 carrying non-synonymous base substitutions or a small in-frame deletion reportedly outstripped the null allele in tomato plants [ 101 , 102 ]. Tomato exhibits two eIF4Es , eIF4E1 and eIF4E2 , eIF(iso)4E, and nCBP .…”
Section: Main Textmentioning
confidence: 99%
“…Recently, we edited eIF4E1 by CRISPR/Cas9 and obtained three alleles, including a nucleotide insertion ( 1INS ) and nine nucleotide deletion ( 9DEL ) within the eIF4E1 protein coding region [ 101 ]. 1INS , containing a frameshift, is considered to be a null allele, and its homozygote showed resistance to the N strain of potato virus (PVY N ).…”
Section: Main Textmentioning
confidence: 99%
“…Consequently, these investigations validated the applicability of CRISPR/Cas9 to augment the development of high-quality tomato crops for higher yield and biomass. Atarashi et al (2020) demonstrated CRISPR/Cas9-mediated mutagenesis in the eIF4E1 gene of a commercial tomato cultivar. In addition to eIF4G, two deletions of three and nine nucleotides (3DEL and 9DEL) and a single nucleotide insertion (1INS) were found in close proximity to regions encoding amino acid residues essential for binding the 5՛ mRNA cap structure.…”
Section: Crispr-based Technologies For Plant Virus Interferencementioning
confidence: 99%